CFD assessment of the wind forces and moments of superstructures through RANS. (December 2022) - Kobayashi, Hiroshi; Kume, Kenichi; Orihara, Hideo; Ikebuchi, Takuro; Aoki, Ichiro; Yoshida, Ryo; Yoshida, Hisafumi; Ryu, Tomohiro; Arai, Yuji; Katagiri, Kosuke; Ikeda, Seiji; Yamanaka, Shota; et al.
Abstract: In addition to wind tunnel tests and regression formulae, numerical simulation has begun to be used at the design stage of ships as a method for estimating the wind force and moments of superstructures. However, no specific approach has been proposed to verify the grid dependence around superstructures, and the degree to which differences in computational conditions affect the results has not yet been systematically clarified. Therefore, a new approach to grid sensitivity analysis is carried out. The effect of some computational conditions on the computed result is investigated using an in-house solver with an overset grid technique with a Japan Bulk Carrier(JBC) model. The method that verifies the grid sensitivity of the hull and the superstructures separately can obtain equivalent results to the method of simultaneously verifying both of them. The grid sensitivity analysis of the superstructures can be performed separately from the hull. The comprehensive comparative study reveals five findings: the blockage effect of the tank size is slight, the steady-state computation is capable of estimating as well as unsteady computation, wall function can be applied to object surfaces, a difference of wind profiles of incident flow can be recovered by the normalization based on the momentum integration in a shear flow, and the Reynolds number effect does not need to be considered if it is greater then 1 . 0 × 1 0 6 . The computations for other ship types are also performed. The computed results show good agreement with the measured data, while the regression formula shows differences from the measured data in some cases. The above study has shown that steady-state CFD analysis is capable and viable in estimating the wind forces and moments of superstructures of a ship model in a wind tunnel for various ship types. Highlights: A comprehensive comparative study of the wind loads of superstructures is conducted. Two different approaches are examined for the grid sensitivity analysis. The computations with various computational conditions are carried out with JBC. The computations for a chemical tanker, a container ship, and a PCC are also performed. CFD analysis is capable and viable in estimating wind loads of various ship types.